Genetics of Chronic Traumatic Encephalopathy - Abdolmohammadi, Bobak; Dupre, Alicia; Evers, Laney; Mez, Jesse (Seminars in Neurology, 2020)
Although chronic traumatic encephalopathy (CTE) garners substantial attention in the media and there have been marked scientific advances in the last few years, much remains unclear about the role of genetic risk in CTE. Two athletes with comparable contact-sport exposure may have varying amounts of CTE neuropathology, suggesting that other factors, including genetics, may contribute to CTE risk and severity. In this review, we explore reasons why genetics may be important for CTE, concepts in genetic study design for CTE (including choosing controls, endophenotypes, gene by environment interaction, and epigenetics), implicated genes in CTE (including APOE, MAPT, and TMEM106B), and whether predictive genetic testing for CTE should be considered.
Keywords: chronic traumatic encephalopathy; genetics; APOE; MAPT; TMEM106B